SIMULATION DESIGN OF AUTOMATIC SLIDING GATE CONTROL DEVICES - I Nengah Ludra Antara; I Nyoman Sutarna; Kadek Agus Mahabojana D.P.; Ida Bagus Puspa Indra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The gate is a means of dividing the land between the house and the road. The gate also serves for security and comfort as a place to live. As a home security, the gate is made high and equipped with a safety lock. With a gate, you will feel comfortable because other people who come can't enter the house directly, and it's often difficult or overwhelmed when opening or closing the gate. In the case of a gate that has a large size and is also heavy, this will overwhelm us so that a lot of energy and time is needed. The automatic gate control device designed is an electric motor that makes it easier for people to open or close the gate by remote control while at home or at work. Based on the results of the design that has been made, the simulation of the automatic sliding gate control device is expected to solve the problems encountered in the field where the dimensions of the gate are 1500mm x 1000mm x 80mm with a weight of 27kg, the electric motor used is reversible AC which has a speed of 1300 RPM, a power of 60 watts and a 1: 60 gearbox which has become 1 part, the speed of the electric motor is transmitted by a gear with a diameter of 78mm, so that the average gate opening and closing speed is 12.52 and 13.21s with a difference of 0.69s, with the The controller used is the AK-T02 module and the AKJ027 remote can work up to a distance of 10 m. It is hoped that making this control device simulation can be a reference in making automatic gate control devices for homes and other gates.